TANGGUNG JAWAB HUKUM PEMERINTAH ATAS KASUS KERACUNAN MASSAL DALAM PROGRAM MAKAN BERGIZI GRATIS (MBG) BERDASARKAN UNDANG-UNDANG NOMOR 17 TAHUN 2023 TENTANG KESEHATAN - Aisyah, Intannur; Dluha, Muhamad; Qorib, Fathul (Program Studi Magister Hukum Universitas Malikussaleh, 2026)
This study aims to examine the legal provisions governing food provision within “the Free Nutritious Meal Program (MBG)” and to analyze the forms of government legal responsibility in the event of mass “food poisoning incidents during its implementation. The MBG program is a government policy supported by Presidential Regulation Number 83 of 2024 concerning the National Nutrition Agency,” which emphasizes the government's role in planning, implementing, supervising, and ensuring the quality and safety of nutritious food provided to program beneficiaries, particularly school-age children who are considered a vulnerable group. “This research employs a normative legal research method supported by statutory and conceptual approaches. Legal materials, both primary and secondary, were analyzed using descriptive qualitative techniques to systematically explain and understand the research issues. The results of the study indicate that although the legal framework concerning government supervision and responsibility has been normatively established, its practical implementation has not been fully effective due to” weak supervisory control, unclear division of authority among institutions, and suboptimal accountability mechanisms. Government negligence in supervision may give rise to administrative and civil legal liability, and under certain circumstances may also lead to criminal liability if it is proven to have caused mass food poisoning. This study highlights the importance of strengthening the supervision system, improving inter-agency coordination, and implementing transparent accountability mechanisms to ensure that the MBG Program can be carried out effectively, safely, and fairly, while providing optimal legal protection for the public, especially children as program beneficiaries. The findings of this study are expected to serve as a basis for policy evaluation and recommendations to improve food safety supervision and legal protection for society.